(untitled) (مجلة إحالات, 2026)
The recent study deals with one of the earlier and great arab reaserchers in Arab Maghreb, who is Abu Musa al-Jazouli. We want in that study to define his great work wich called « Al –Mokadima Al-jazoulia (Introduction to Grammar) to expose his contribution and effort with critics, comparison and annalysis.to state at the end of this work that Abu Musa al-Jazouli is one of the greatest arab grammarian in arab maghreb as the grammarians of the Arab Orient.